Pengembangan Media Magic Star Box untuk Meningkatkan Kemampuan Motorik Kasar Anak Usia Dini. - Audrey Fadillah; Rosa Imani Khan; Ridwan Ridwan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The background of this research highlights the crucial role of vocabulary mastery in children’s language development, which significantly impacts their social interactions and learning processes. This study focuses on developing the Magic Star Box as a learning medium aimed at enhancing the gross motor skills of children aged 4–5 years. The Magic Star Box is an adaptation of stop-motion media, designed to create an engaging and enjoyable learning atmosphere by integrating words and images. The research applies a Research and Development (R&D) method, simplified into four stages: identifying potentials and problems, collecting data, designing the product, and validating the design. Validation from subject matter experts and game design experts indicated that the Magic Star Box is feasible for improving children’s vocabulary. This medium is expected to provide an innovative, engaging, and effective learning solution for young learners